(1/8)x + (1/16)x = 1
(2/16)x + (1/16)x = 1
(3/16)x = 1
x = 16/3 = 5.33333 hrs
Answer:
x=2
x=-5
Step-by-step explanation:
You need to get everything on one side to have a quadratic equation:
x^2+6x-4 -(3x+6) = x^2+3x-10
All factors of 10 are 1*10 and 2*5.
5-2 = 3 and 5*-2 = -10
Factoring x^2+3x-10 gives us (x-2)(x+5)
x=2
x=-5
Answer:
(3y - 2)(2y - 7)
Step-by-step explanation:
To factorise the quadratic
Consider the factors of the product of the coefficient of the y² term and the constant term which sum to give the coefficient of the y- term
Product = 6 × 14 = 84 and sum = - 25
The required factors are - 4 and - 21
Use these factors to split the y- term
6y² - 4y - 21y + 14 ( factor the first/second and third/fourth terms )
2y(3y - 2) - 7(3y - 2) ← factor out (3y - 2) from each term
= (3y - 2)(2y - 7) ← in factored form
Answer:
31/40
Step-by-step explanation:
It cannot be reduced anymore. It is already in simplest form.